IMPLEMENTASI KONSEP HUKUM HADLANAH DALAM PENGASUHAN ANAK ANGKAT (Tabanni): (Studi Kasus di Desa Pabuaran, Kecamatan Pabuaran, Kabupaten Subang) - Ramdhani, Muhammad Ally; Gussevi, Sofia; Tadjudin , Azi Ahmad (Al-Usroh, 2025)
This research examines the implementation of the hadlanah concept within the practice of adopted child upbringing (tabanni) by two families in Pabuaran Village, Pabuaran District, Subang Regency. Hadlanah, as a concept of child-rearing in Islamic law, possesses distinct characteristics, particularly in the context of adopted children born out of wedlock. This study analyzes the issue from both Islamic law and positive law perspectives, involving interviews with adoptive families, religious leaders, and community figures. The findings indicate that both families harbored good intentions in caring for the children but lacked a complete understanding of the boundaries of hadlanah, including aspects related to nasab (lineage), aurat (intimate parts), mahram (unmarriageable kin), and inheritance rights. The research also found that knowledge regarding the rights and obligations between biological parents, adoptive parents, and the child remained weak, both under religious and state law. A synergy between understanding Islamic law and national law is crucial to ensure the best protection for the child.